Soluble Neprilysin ― Cardiac Function and Outcome in Hypertrophic Cardiomyopathy ― - Yoshihisa, Akiomi (Circ Rep, 2019)
Background: Circulating soluble neprilysin (sNEP) predicts outcome in heart failure (HF) patients with reduced ejection fraction (EF), but not in those with preserved EF. We examined sNEP in patients with hypertrophic cardiomyopathy (HCM), and their correlations with other biomarkers, cardiac function, and clinical outcome. Methods and Results: We examined the associations between sNEP and the laboratory and echocardiography parameters in the HCM patients (n=93). Regarding the laboratory data, sNEP had a significant positive correlation with B-type natriuretic peptide (BNP; R=0.326, P=0.003), but not with troponin I. As for the echocardiographic parameters, sNEP negatively correlated with left ventricular EF (R=−0.283, P=0.009) and right ventricular fractional area change (R=−0.277, P=0.012), but not with left ventricular mass. Next, we prospectively followed up on the patients for cardiac events, including worsening HF or cardiac death, and all-cause mortality. On Kaplan-Meier analysis (mean follow-up, 1,021 days), the cardiac event rate and all-cause mortality were similar between the higher sNEP group (sNEP ≥median level of 1.43 ng/mL, n=46) and lower sNEP group (sNEP <1.43 ng/mL, n=47). On Cox proportional hazard analysis, sNEP was not a predictor of cardiac event or all-cause mortality. Conclusions: Soluble neprilysin appears to correlate with BNP and cardiac systolic function, but it is not significantly associated with prognosis in HCM patients.